2022
DOI: 10.3389/fmicb.2022.814831
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Differences in Antibiotic Resistance, Biofilm Formation, Mobility, and Virulence of Clinical Enterobacter cloacae Complex

Abstract: Due to the lack of research on the characteristics of different clusters of Enterobacter cloacae complex (ECC), this study aimed to characterize and explore the differences among species of the ECC. An analysis based on hsp60 showed that Enterobacter hormaechei was predominant in ECC. Interestingly, the antibiotic resistance rates of clusters were different, among which E. hormaechei subsp. steigerwaltii (cluster VIII) and Enterobacter cloacae IX (cluster IX) possessed high resistant rates to ciprofloxacin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…In the present study, diverse species of ECC were identified in patients, including four recently described species ( E. bugandensis , E. chengduensis , E. roggenkampii , and E. mori ; Zhu et al, 2011 ; Doijad et al, 2016 ; Sutton et al, 2018 ; Wu et al, 2019 ). Among the ECC isolates from South Korea, E. hormaechei was the predominant species, as was also the case in a recent study from China ( Liu et al, 2022 ). Unlike the results from China, E. hormaechei subsp.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, diverse species of ECC were identified in patients, including four recently described species ( E. bugandensis , E. chengduensis , E. roggenkampii , and E. mori ; Zhu et al, 2011 ; Doijad et al, 2016 ; Sutton et al, 2018 ; Wu et al, 2019 ). Among the ECC isolates from South Korea, E. hormaechei was the predominant species, as was also the case in a recent study from China ( Liu et al, 2022 ). Unlike the results from China, E. hormaechei subsp.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, many papers have mistakenly labeled the clinical isolates as E. cloacae or reported different species as ECC indiscriminately ( Hong et al, 2018 ; Sutton et al, 2018 ). Meanwhile, hsp60 gene sequences contain enough variation among the species of ECC for these distinctions to be made, indeed this gene has been recently utilized for ECC species identification ( Hoffmann and Roggenkamp, 2003 ; Liu et al, 2022 ; Sato et al, 2022 ). However, there are few data on the species distribution of ECC and species characteristics ( Liu et al, 2022 ), particularly in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we did not observe a significant difference between E. hormaechei and the other species in terms of demographic data, comorbidities, therapeutic devices and procedures, and clinical outcomes (30-day and 100-day mortality). With regard to the virulence of specific clusters, Liu et al reported the virulence of cluster I strains was significantly higher than that of the other cluster strains according to the results of the Galleria mellonella infection model [ 46 ]. Cluster II ( E. kobei ) has strong biofilm formation ability under nutrient-deficient conditions but is associated with low virulence and pathogenicity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the virulence of specific clusters, Liu et al reported the virulence of cluster I strains was significantly higher than that of the other cluster strains according to the results of the Galleria mellonella infection model [ 46 ]. Cluster II ( E. kobei ) has strong biofilm formation ability under nutrient-deficient conditions but is associated with low virulence and pathogenicity [ 46 ]. However, the case number of cluster I in our study is too small to obtain enough clinical finding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the temperature and time factors, the study showed that the individual characteristics of the strains significantly affect the production of biofilm. The ability to produce biofilm by E. hormaechei bacteria was confirmed by the studies of Liu et al (2022) [ 49 ]. The differences in biofilm production by B. cereus depending on environmental factors have been described in numerous studies.…”
Section: Discussionmentioning
confidence: 81%